The essential kinase TgGSK regulates centrosome segregation and endodyogeny in Toxoplasma gondii - Amanda Krueger; Sofia Horjales; Chunlin Yang; William J. Blakely; Maria E. Francia; Gustavo Arrizabalaga (mSphere)
ABSTRACT Intracellular replication is crucial for the success of apicomplexan parasites, including Toxoplasma gondii. Therefore, essential players in parasite replication represent potential targets for drug development. We have characterized TgGSK, a glycogen synthase kinase homolog that plays an important role in Toxoplasma endodyogeny. We have shown that TgGSK has a dynamic localization that is concurrent with the cell cycle. In non-dividing parasites, this kinase is highly concentrated in the nucleus. However, during division, TgGSK displays a cytosolic localization, with concentration foci at the centrosomes, a key organelle involved in parasite division, and the basal end. Conditional knockdown of TgGSK determined that it is essential for the completion of the lytic cycle and proper parasite division. Parasites lacking endogenous protein levels of TgGSK exhibited defects in division synchronicity and the segregation of the nucleus and apicoplast into forming daughter cells. These phenotypes are associated with defects in centrosome duplication and fission. Global phosphoproteomic analysis determined TgGSK-dependent phosphorylation of RNA-processing, basal end, and centrosome proteins. Consistent with the putative regulation of RNA-processing proteins, global transcriptomic analysis suggests that TgGSK is needed for proper splicing. Finally, we show that TgGSK interacts with GCN5b, a well-characterized acetyltransferase with roles in transcriptional control. Conversely, GCN5b chemical inhibition results in specific degradation of TgGSK. Thus, these studies reveal the involvement of TgGSK in various crucial processes, including endodyogeny and splicing, and identify acetylation as a possible mechanism by which this essential kinase is regulated.IMPORTANCEWhile infection with the parasite Toxplasma gondii is largely asymptomatic in healthy adults, severe disease and death can result in immunocompromised individuals and in those infected congenitally. With minimal treatments for toxoplasmosis available, it is crucial to study parasite-specific processes to identify new drug targets. This study investigated the protein TgGSK, uncovering its essentiality for parasite proper division and survival. We performed an in-depth study of the functional role of this kinase. Importantly, TgGSK was shown to bear higher homology to plant proteins than its mammalian counterparts, which may allow for specific targeting of this protein.